Analysis of Student's Misconceptions in Science Subjects Through Experimental Methods - Farida Farida; Nur Khosiah (Universitas Muhammadiyah Sidoarjo, 2022)
Science lessons are material that students need to understand. Therefore, when learning science in schools it is very important to be discussed and educated so that students can share scientific thinking attitudes. The problem that occurs at this time at MI Riyadlus Sholihin is students' misconceptions about science lessons due to the monotony of the methods used so that students do not understand the material being studied. The purpose of this researcher is to use the experimental method to find out the problems that arise in students' misconceptions in class 4 MI Riyadlus Sholihin Leces Probolinggo. So that learning activities become more active, it can be seen that students can collaborate in groups and are formed as a result of which learning objectives can be achieved practically. The method used in this study is a qualitative research using a descriptive approach with data collection methods of observation, interviews, and documentation. In implementing the science experimental learning method in class 4 MI Riyadlus Sholihin Pondok Wuluh Leces Probolinggo using student work. The teacher gives multiple choice questions, evaluates verbally through question and answer after analyzing the material, and directs students to report their observations in groups after experiments related to the properties of light in science learning.